مقاطعة المنتجات الداعمة لإسرائيل بين التضامن الأخلاقي وواقع السوق: تحليل نقدي متعدد الأبعاد لفجوة الوعي الرمزي والأثر البنيوي في سلوك المستهلكين في الجنوب العالمي: Boycotting Products Pro-Israel: A Multi-Dimensional Critical Analysis of the Symbolic Awareness Gap and Structural Impact on Consumer Behavior in the Global South - Annajaty, Abdulloh Yahya; Isman, Isman; Alam, Azhar (Universitas Muhammadiyah Surakarta, 2025)
Campaigns to boycott products related to Israel or support them are on the rise in the countries of the Global South as a political consumption behavior that combines moral solidarity and symbolic pressure on companies. However, the power of the campaign in the public sphere does not necessarily mean the power of the impact in the market or in the political-economic structures that support the conflict. This article aims to provide a multi-dimensional critical analysis of symbolic awareness gaps and structural impacts based on the current literature (2021–2025) on boycotts, political consumption, and digital activism, by reinforcing the theoretical framework with quantitative and qualitative evidence from studies in East Asia (Indonesia and Malaysia). This article uses a composite approach that includes: (1) a selective methodological review of recent research in accordance with defined transparency standards, (2) an interpretive model that combines Planned Behavior Theory (SDP), Social Identity Theory (SIT), and a political economy approach to global value chains (GVCs), (3) comparative analysis supported by field evidence on the role of religiosity, perceived efficiency, and and local alternatives in converting intentions into actual behaviors. The article concludes that to reduce the gap, boycotts must be transformed from moral indicators to market governance tools based on supply chain transparency, support programs for local alternatives, and ESG accountability mechanisms.